2019
DOI: 10.1016/j.cub.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Viscoelasticity Is Regulated by Mechanosensitive E-cadherin Turnover

Abstract: Graphical AbstractHighlights d Mechanical stress releases p120-catenin from apical junctions d Loss of p120-catenin increases endocytic E-cadherin turnover d Loss of p120 speeds stress-dependent remodeling of the junctional network d Mechanical stress dependence of E-cadherin turnover sets tissue viscoelasticity SUMMARY Studying how epithelia respond to mechanical stresses is key to understanding tissue shape changes during morphogenesis. Here, we study the viscoelastic properties of the Drosophila wing epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 56 publications
(92 reference statements)
8
116
2
Order By: Relevance
“…(B) Junctions between migrating astrocytes display planar-polarized dynamics where N-cadherin is endocytosed at the rear of the junctions, then recycled to the front is disrupted. Subtle changes in dorsal closure and wing size were observed in p120 ctn null Drosophila mutants, 26,27 but these animals were viable and fertile, consistent with observations in Caenorhabditis elegans mutant animals. 28 However, p120 ctn mutant animals were sensitized to the effects of cadherin or α-catenin alleles.…”
Section: Regulating Cadherin Endocytosis Through P120-cateninsupporting
confidence: 85%
See 1 more Smart Citation
“…(B) Junctions between migrating astrocytes display planar-polarized dynamics where N-cadherin is endocytosed at the rear of the junctions, then recycled to the front is disrupted. Subtle changes in dorsal closure and wing size were observed in p120 ctn null Drosophila mutants, 26,27 but these animals were viable and fertile, consistent with observations in Caenorhabditis elegans mutant animals. 28 However, p120 ctn mutant animals were sensitized to the effects of cadherin or α-catenin alleles.…”
Section: Regulating Cadherin Endocytosis Through P120-cateninsupporting
confidence: 85%
“…This was recently supported by in vivo studies conducted in the embryonic Drosophila wing. Here, Iyer et al identified a pool of DE‐cadherin that turned over on a minutes‐long time scale, consistent with the time scales for cadherin endocytosis. Notably, the mobile fraction of this cadherin pool was significantly increased in p120 ctn null mutants, implying that cadherin endocytosis was being increased.…”
Section: Regulating Cadherin Endocytosis Through P120‐cateninsupporting
confidence: 78%
“…In zebrafish, these observations were further confirmed by the use of ferromagnetic oil droplets (FDs) to directly measure tissue viscosity within the PSM (Box 1; Fig 2F), pointing at the possibility that the mesoderm transits from a fluid into a more solid-like state during maturation along its anterior-posterior axis (Serwane et al, 2017;Mongera et al, 2018). Similarly, in the Drosophila pupal wing epithelium, the rate of cell elongation over time represents a reliable readout of the viscoelastic behaviour of the tissue during wing deformation (Iyer et al, 2019). For example, the viscosity of Xenopus embryonic tissues, when measured by explant shape analysis (ESA, Box 1), appears to be linearly correlated with the surface tension of the tissue, a relationship defined by the rate of cell rearrangements within the tissue (David et al, 2014).…”
Section: Of 13mentioning
confidence: 67%
“…By analysing variations in cell shape within the forming ventral furrow in Drosophila, solid-like areas within the furrow were shown to correspond to less elongated and variable cell shapes, while more fluid-like areas exhibit longer and more variable cell shape that allows more frequent cell rearrangements (Atia et al, 2018). Similarly, in the Drosophila pupal wing epithelium, the rate of cell elongation over time represents a reliable readout of the viscoelastic behaviour of the tissue during wing deformation (Iyer et al, 2019). While the theoretical considerations and experimental observations discussed above clearly show a link between certain cellular parameters, such as cell density, rearrangements and shape, with the tissue phase state and its resulting morphogenetic capacity, remarkably little is yet known on how these parameters are spatiotemporally regulated within the developing organism.…”
Section: Tissue Rheology Defined By Cellular Topologymentioning
confidence: 99%
See 1 more Smart Citation